PENGARUH DIMENSI KUALITAS PELAYANAN RITEL TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN: Studi Kasus Konsumen Mirota Kampus Di Yogyakarta - Ulfan Ulfan; IBN Udayana; Bernadetta Diansepti Maharani (Jurnal Riset Rumpun Ilmu Ekonomi, 2022)
This study aims to examine the Physical Aspects, Personality Interaction, Problem Solving, mediated by Customer Satisfaction against Customer Loyalty. The data used in this study used data obtained from questionnaires distributed to customers at Mirota Campus, DI Yogyakarta. The number of questionnaires distributed in this study to 220 respondents. The research data were analyzed using multiple linear regression analysis using the SPSS 25 program. The results of this study indicate (X1) Physical Aspects not have a positive effect on (Z) Customer Satisfaction. (X2) Personality Interaction has a positive effect on (Z) Customer Satisfaction. (X3) Problem Solving has a positive effect on (Z) Customer Satisfaction. (Z) Customer Satisfaction directly has a positive effect on (Y) Customer Loyalty. (X1) Physical Aspects through (Z) Customer Satisfaction has a significant influence on (Y) Customer Loyalty. (X2) Personality Interaction through (Z) Customer Satisfaction has a significant influence on (Y) Customer Loyalty. (X3) Problem Solving through (Z) Customer Satisfaction has no significant effect on (Y) Customer Loyalty and service quality mediated by costumer satisfaction (Z) on costumer loyalty (Y) has a positive effect.